Information literacy competency standards for higher education and their correlation with the cycle of knowledge generation - Uribe Tirado, Alejandro; Castaño Muñoz, Wilson (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
This article considers the cycle of knowledge generation proposed by Nonaka and Takeuchi and sets out how the different indicators and expected results within the information literacy (IL) standards used in higher education contribute to this cycle. After analyzing each standard and its interrelation with the four options to generate knowledge of Nonaka’s cycle, it was identified that these standards are more geared to the generation of explicit knowledge, and therefore, it is necessary to work on other activities, and new proposed standards of IL that promote the generation of tacit knowledge and information processes needed.